CHEMICALLY MODIFIED SMECTITES - Komadel P. (My University, 2003)
This paper summarizes recent results obtained on chemical modifications of smectites. These include replacement of exchangeable cations with protons, a process connected with smectite autotransformation - attack of protons on the layers and liberation of central atoms from the octahedral and tetrahedral sheets, causing modification of the acid sites on the particles. More severe modifications occur during dissolution in inorganic acids, when the layers are dissolved and threedimensional amorphous silica is formed. The negative charge on the smectite layers can be increased via reduction of structural Fe(III) to Fe(II) or decreased via fixation of small exchangeable cations, such as Li+, upon treatment at elevated temperatures. Heating for 24 h at different temperatures between 100 and 300ºC leads to a series of chemically similar materials of different charge, prepared from the same parent mineral. Such series are suitable for investigation of the effect of the layer charge on selected properties of smectites. Fe(II) can be partly stabilized in reduced smectites by Li fixation upon heating.
Keywords: H-smectites; acid dissolution; charge modification; Li fixation; reduction